Effects Of Hormonal Supplements In Women with Poor Ovarian Response Undergoing Assisted Reproductive Technology - Silan Melis Bozan; Gurkan Bozdag (Gynecology Obstetrics & Reproductive Medicine)
Poor ovarian response remains one of the major challenges of assisted reproductive technology. Over the years, various interventions have been proposed to improve reproductive outcomes in poor responders, yet few have been shown to be beneficial. Recent studies indicate that hormonal pretreatments might increase clinical pregnancy rate, live birth rate and the number of oocytes retrieved in women with poor ovarian response undergoing assisted reproductive technology. Areas covered: Following extensive research of the up to date literature, this review aims to cover current considerations and controversies regarding the use of hormonal supplements such as dehydroepiandrosterone, transdermal testosterone and growth hormone. Expert opinion: There is limited data for the validity of using growth hormone and androgens or androgen modulating agents during assisted reproductive technology cycles in women suffering from poor ovarian response. However, there is a need to support the available data with further randomized controlled trials seeking for live birth rate as the primary outcome.